2018
DOI: 10.1007/s10661-018-6637-z
|View full text |Cite
|
Sign up to set email alerts
|

Granulometric and pebble morphometric applications to Benin Flank sediments in western Anambra Basin, Nigeria: proxies for paleoenvironmental reconstruction

Abstract: Integrated granulometric and pebble morphometric study of Late Cretaceous rocks of the Benin Flank, Nigeria, were used to delineate depositional process and environment of the rocks in the study area. Granulometric analysis reveals that the sandstones of the Lokoja Bassange Formation have an average graphic mean (Mz) of 0.59Φ (coarse grains), inclusive graphic standard deviation (δi) of 1.36Φ (poorly sorted), graphic kurtosis (Ka) of 1.12Φ (leptokurtic), and inclusive graphic skewness (Ski) of - 0.14Φ (stongly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…The size and shape of clastic sediments have been related to the processes of transport and deposition. It has been shown and proved that pebble morphometric parameters may be helpful, as additional indicators, in deciphering the processes of transport and depositional environment (e.g., Sneed & Folk, 1958;Lutig, 1962;Sames, 1966;Dobkins & Folk, 1970;Stratten, 1974;Gale, 1990Gale, , 2021Widera, 2010;Okoro et al, 2012;Odumodu & Israel, 2014;Ocheli et al, 2018;Madi & Ndlazi, 2020;Oluwajana et al, 2021).…”
Section: Pebble Morphogenesis For Interpretation Of Depositional Sett...mentioning
confidence: 99%
See 1 more Smart Citation
“…The size and shape of clastic sediments have been related to the processes of transport and deposition. It has been shown and proved that pebble morphometric parameters may be helpful, as additional indicators, in deciphering the processes of transport and depositional environment (e.g., Sneed & Folk, 1958;Lutig, 1962;Sames, 1966;Dobkins & Folk, 1970;Stratten, 1974;Gale, 1990Gale, , 2021Widera, 2010;Okoro et al, 2012;Odumodu & Israel, 2014;Ocheli et al, 2018;Madi & Ndlazi, 2020;Oluwajana et al, 2021).…”
Section: Pebble Morphogenesis For Interpretation Of Depositional Sett...mentioning
confidence: 99%
“…Pebble morphometric analysis is a sedimentological approach that has been successfully applied by several workers for deciphering the palaeoenvironments and depositional settings of similar formations and basins in Nigeria and other parts of the world (e.g., Sames, 1966;Hubert, 1968;Dobkins & Folk, 1970;Nwajide & Hoque, 1982;Gale, 1990Gale, , 2021Olugbenro & Nwajide, 1997;Ogala et al, 2010;Widera, 2010;Okoro et al, 2012; A -A simplified regional geological surface map of the Niger Delta Basin showing the location of the studied outcrop (marked as a red star) in the northern delta area (reprinted from Ogbe, 2021); B -A schematic NE-SW cross-section through the Niger Delta Basin in south-eastern Nigeria (reprinted from Ogbe, 2021;Ogbe & Osokpor, 2021); note the position of the vertical line AB depicting stratigraphical successions in the Niger Delta Basin; for a detailed stratigraphy see Figure 2. Nton & Adamolekun, 2016;Ocheli et al, 2018;Madi & Ndlazi, 2020;Oluwajana et al, 2021). Similarly, Odumodu and Israel (2014) and Onyemesili and Odumodu (2019) used this sedimentological approach with eroded pebbles in the interpretation of the Ogwashi Formation and concluded that the sediments of this unit formed in a fluvial environment.…”
mentioning
confidence: 99%
“…Most of the deep wells constructed in CRB seemed to be positioned on the Benin Formation, as the outcrops of the Ajali Formation is narrow. The aquifers of Benin Formation are confined in some places producing artesian conditions [44,[115][116][117][118] . As a result of poor groundwater conditions in CRB, people largely depend on surface water sources, waterborne diseases like guinea worm contagion, is rather widespread, especially in Abakaliki, Enyimba, and Uburu areas [44] .…”
Section: The Asu River Ezeaku Awgu Mamu and Nkporo Assemblagesmentioning
confidence: 99%
“…However, reports on the depositional environment and provenance of sands of the Ajali Formation on the western flank of the Anambra Basin, south of Ifon are limited. Many researchers have conducted different studies on sediments in different parts of the world to interpret the depositional process and environment of such sediments (Ocheli et al, 2018). The grain-size distribution of sediment reflects both the hydrodynamic conditions and the grain-size population of sediments available from the source area (Bjørlykke, 2010).…”
mentioning
confidence: 99%
“…Tijani et al, 2010 revealed that Ajali Sandstone in the Anambra Basin was deposited under a fluvial/river system-dominated sedimentary process. Ocheli et al (2018) established a fluvial to shallow marine environment for the Ajali Sandstone in the western flank of the Anambra Basin. Ladipo (1985), Tijani et al, (2010), and Ogbahon and Opeloye (2014) observed that Ajali Sandstone has quartz greater than 90% with very little clay matrix, indicating a predominant basement source.…”
mentioning
confidence: 99%